Implementation of Government Policy to Increase Competitiveness Cirebon City SMEs (Case Study of UKM Assisted by DKUKMPP Cirebon City) - Fauziyyah Melati Andriana; Moch Zidan Nurfadilah; Mukarto Siswoyo (Indonesian Journal of Business Analytics, 2024)
The implementation of government policies to enhance the competitiveness of Small and Medium Enterprises (SMEs) in Cirebon City faces various challenges, especially related to the effectiveness of resources. Based on Edward III’s policy implementation theory, there are four key elements that influence the success of policy implementation: communication, resources, the disposition or attitude of implementers, and bureaucratic structure. This research uses a descriptive qualitative method, with data collected through in-depth interviews, observations, and documentation. In the context of Cirebon City, the main issue lies in the suboptimal management of resources, including limited access to funding, low labor force, and lack of supporting facilities and infrastructure. This impacts the limited ability of assisted SMEs to compete in an increasingly competitive market. This study aims to analyze the implementation of government policies, identify the barriers faced, and provide strategic recommendations to improve policy effectiveness. Through a comprehensive approach, this study is expected to provide insights to strengthen the competitiveness of SMEs as a driving force of the local economy in Cirebon City.